An Atomic Force Microscopy (AFM) Modelling in Fractional Order: Nonlinear Control System Design - Yamaguchi, Patricia S. [UNESP]; Tusset, Angelo M.; Ribeiro, Mauricio A.; Balthazar, Jose M. [UNESP] (Springer Nature, 2022)
The atomic force microscope (AFM) on the nanoscale measurements comes from nanotechnology and is currently a multidisciplinary field of research. The present research proposal aims to contribute to scientific research on AFM considering that the system is operating in the intermittent mode and the contact of the tip with sample generates a damping represented by squeeze-film damping, and that the damping dynamics of the squeeze-film damping can be represented by fractional calculus through numerical simulation and dynamic analysis to prove chaotic regimes. To suppress chaotic behavior, we will use and analyze two control strategies, the SDRE (Riccati Equation Dependent States) and OLFC (Linear Control for Optimum Feedback) controls.
Keywords: AFM; Chaos; Derivative fractional order; Optimal linear control; SDRE control